The Effect of Viral Marketing, Online Customer Reviews, and Online Customer Ratings on Product Purchase Decisions at Bukalapak (A Case Study of Students at Muhammadiyah University Bengkulu) - Minandar, Muhammad Riski; Yulinda, Ade Tiara (Proceedings Series on Social Sciences & Humanities, 2025)
Consumer purchasing decisions on e-commerce platforms are influenced by various factors, some of which are viral marketing, online customer reviews, and online customer ratings. This study aims to analyze the influence of viral marketing, online customer reviews, and online customer ratings on product purchasing decisions on Bukalapak, with a case study of students at Muhammadiyah University Bengkulu. This study employs a quantitative method with a survey approach. The study population consists of all students at Muhammadiyah University of Bengkulu. The sample size is 140 students. Data was collected through a questionnaire distributed to students at Muhammadiyah University of Bengkulu who have made purchases on Bukalapak. Data analysis was conducted using multiple linear regression techniques. The results of the study indicate that viral marketing has a positive and significant influence on purchasing decisions, meaning that the wider the reach and effectiveness of viral marketing, the higher the likelihood of consumers making a purchase. Online customer reviews also have a positive and significant influence on purchasing decisions, indicating that good customer reviews can increase consumer trust and interest in purchasing products. Additionally, online customer ratings have a positive and significant influence on purchasing decisions, indicating that high product ratings can increase consumer confidence in making purchasing decisions. This study confirms that viral marketing, online customer reviews, and online customer ratings are the main factors influencing product purchase decisions on Bukalapak. Therefore, businesses on Bukalapak are advised to utilize viral marketing strategies, encourage customers to provide positive reviews, and maintain product ratings to increase consumer purchase decisions.